The Social Construction of Bughāt as a Technology of Abbasid Hegemony in al-Māwardī’s al-Aḥkām al-Sulṭāniyyah - Hikami, Abdullah Faqih; Fikri, Syarifuddin Ala Dzil (An-Nur International Journal of Islamic Thought, 2025)
The Islamic law of rebellion (bughāt) is traditionally interpreted as a protective framework or a neutral theological derivation designed to regulate internal political conflicts. Challenging these static interpretations, this study employs a genealogical deconstruction synthesized with social constructionism and power/knowledge frameworks to investigate al-Māwardī’s al-Aḥkām al-Sulṭāniyyah as an artifact of imperial survival. Findings reveal that al-Māwardī’s formulation of bughāt functions as a sophisticated "technology of power" engineered to mitigate the material impotence of the Abbasid Caliphate under Buwayhid hegemony. By constructing "legal fictions" of symbolic sovereignty, the text weaponizes the ambiguity between rebellion and banditry (ḥirābah). This architecture of exclusion utilizes the criteria of military strength (shawka) and plausible interpretation (ta’wīl) not to shield rebels, but to discipline the social body and criminalize dissenters who lack state-mirrored organizational structures. Consequently, the law transforms political opposition into a criminalized "non-subject" status, ensuring the state’s monopoly on legitimate violence. This research concludes that classical fiqh is a historically contingent tool of hegemonic legitimation, exposing the inherent exclusionary mechanisms that underpin the preservation of centralized authority.